ANALISIS BIBLIKA PELAYANAN DIAKONIA BERDASARKAN KISAH PARA RASUL 6:1-7 DAN RELEVANSINYA BAGI PELAYANAN GEREJA MASA KINI - Selvianty Selvianty; Mersy Tandi Benyamin, Sri Dewi T. R., Yulsri Parerung, Gita Pala’langan (ADISAM PUBLISHER, 2023)
This research aims to examine the role and principles of diakonia ministry as found in Acts 6:1- 7 and evaluate their relevance in the context of contemporary church ministry. The research methodology involves the analysis of the text of Acts 6:1-7, biblical literature review, and interviews with church leaders. The findings of the study indicate that Acts 6:1-7 illustrates the significance of diakonia ministry in addressing issues within the early church. Principles such as the selection of deacons, serving the needy, and promoting unity within the church are the primary focus. Furthermore, the research analyzes how these principles can be applied in the context of modern church ministry, particularly in addressing the challenges and needs of today’s society. The research concludes that the diakonia principles found in Acts 6:1-7 remain relevant in contemporary church ministry. Implementing these principles can help churches be more effective in serving their congregations and the broader community. This conclusion is expected to serve as a foundation for churches to strengthen their diakonia ministry and make a positive impact in society.